2019
DOI: 10.1093/mnras/stz3533
|View full text |Cite
|
Sign up to set email alerts
|

Multiband optical flux density and polarization microvariability study of optically bright blazars

Abstract: We present the results of flux density, spectral index, and polarization intra-night monitoring studies of a sample of eight optically bright blazars, carried out by employing several small to moderate aperture (0.4 m to 1.5 m diameter) telescopes fitted with CCDs and polarimeters located in Europe, India, and Japan. The duty cycle of flux variability for the targets is found to be ∼ 45 percent, similar to that reported in earlier studies. The computed two-point spectral indices are found to be between 0.65 to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 103 publications
1
7
0
Order By: Relevance
“…Therefore, the radiation and polarization signatures that we present in this paper can happen on very short time scales. Interestingly, such micro-variability patterns have been reported in observations (e.g., Pasierb et al 2019). On the other hand, in a striped jet morphology, the magnetic stripes are created at the central engine and propagate out along with the jet.…”
Section: Implications For Observationssupporting
confidence: 58%
See 1 more Smart Citation
“…Therefore, the radiation and polarization signatures that we present in this paper can happen on very short time scales. Interestingly, such micro-variability patterns have been reported in observations (e.g., Pasierb et al 2019). On the other hand, in a striped jet morphology, the magnetic stripes are created at the central engine and propagate out along with the jet.…”
Section: Implications For Observationssupporting
confidence: 58%
“…Therefore, we do not expect any large ( 90 • ) PA rotations from reconnection in kink instabilities or magnetic turbulence. Very interestingly, the blazar micro-variability, which may originate from reconnection in magnetic instabilities/turbulence, mostly shows small PA fluctuations (Pasierb et al 2019). In contrast, in the striped jet scenario, a large region of anti-parallel magnetic field lines with small guide fields is probable.…”
Section: Implications For Observationsmentioning
confidence: 97%
“…Employing enhanced F-and nested ANOVA tests, the authors found the source to vary on intra-night timescales for three nights. Finally, Pasierb et al (2020) found no INV in the BVR-bands during a single night of monitoring (duration of about 3.7 hr, F-test employed).…”
Section: Duty Cyclementioning
confidence: 87%
“…Annihilation of magnetic field lines at the reconnection sites within the jet plasma can also impart energy to the particles (Giannios 2013;Sironi et al 2015); this scenario is supported by the recent detection of minutelike variability at GeV energies for the blazar 3C 279 (Shukla & Mannheim 2020). On the other hand, flux changes on the intranight timescales have also been associated with variable Doppler boosting factors related to changes in the viewing angle of the emitting plasma (e.g., Gopal-Krishna & Wiita 1992), although in such a scenario frequency-independent variability is expected (see, in this context, Pasierb et al 2020).…”
Section: Introductionmentioning
confidence: 83%